2024
DOI: 10.3390/antibiotics13030197
|View full text |Cite
|
Sign up to set email alerts
|

The Fragmented Picture of Antimicrobial Resistance in Kenya: A Situational Analysis of Antimicrobial Consumption and the Imperative for Antimicrobial Stewardship

Aarman Sohaili,
Judith Asin,
Pierre P. M. Thomas

Abstract: Antimicrobial resistance (AMR) jeopardizes the effectiveness of essential antimicrobial agents in treating infectious diseases. Accelerated by human activities, AMR is prevalent in Sub-Saharan Africa, including Kenya, due to indiscriminate antibiotic use and limited diagnostics. This study aimed to assess Kenya’s AMR efforts through a situational analysis of policy efficacy, interventions, and implementation, culminating in recommendations for strengthening mitigation. Employing two methodologies, this study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In Brazilian intensive care units, for example, the consumption of Reserve AB reached 40% [17]. Consistently and uniformly evaluating antimicrobial consumption is a challenge in many countries, such as those in Latin America [21] and Africa [22]. The combined efforts of the most diverse areas of science are recommended, as resistance mechanisms are known for all ABs used in the clinic, and the discovery of promising new classes to treat bacterial infections is increasingly rare [23].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazilian intensive care units, for example, the consumption of Reserve AB reached 40% [17]. Consistently and uniformly evaluating antimicrobial consumption is a challenge in many countries, such as those in Latin America [21] and Africa [22]. The combined efforts of the most diverse areas of science are recommended, as resistance mechanisms are known for all ABs used in the clinic, and the discovery of promising new classes to treat bacterial infections is increasingly rare [23].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review indicated that the general increase in the consumption of ABs in LMICs, especially those in the Watch category, worsened during the COVID-19 pandemic [18]. Consistently and uniformly evaluating antimicrobial consumption is a challenge in many countries, such as those in Latin America [19] and Africa [20]. Combined efforts in the most diverse areas of science are necessary, as resistance mechanisms are known for all marketed ABs, and the discovery of promising new classes to treat bacterial infections is increasingly rare [21].…”
Section: Introductionmentioning
confidence: 99%